The Role of Competence, Salary, Work Environment, Job Satisfaction, Compensation, Communication on Elementary School Teacher Performance - Hariyasasti, Yayuk; Purwanto, Agus (AGUSPATI Research Institute, 2025)
In the world of education, the relationship between teachers and management is a key factor in creating a harmonious and productive work environment. However, many elementary schools face challenges in maintaining conducive industrial relations. One of the main problems is the imbalance between teacher competence and the salary given. Many teachers feel that the compensation received is not commensurate with their level of expertise and responsibility, which can ultimately reduce motivation and performance. Based on the discussion above, it can be concluded that conducive industrial relations are highly dependent on variables such as competence, salary, work environment, job satisfaction, compensation, and communication. These factors play an important role in creating a harmonious relationship between teachers and management, which ultimately contributes to improving teacher performance